PENINGKATAN KESADARAN EKOLOGIS MELALUI EDUKASI EKOWISATA MANGROVE DI KAWASAN KONSERVASI MANGROVE DAN BEKANTAN (KKMB) TARAKAN - Khadami, Faruq; Luthfiyana, Novi; Sujatmiko, Karina Aprilia; Puspaningrum, Mika Rizki; Rahmawani, Dori; Purnomo, Maharani Rachmawati; Azharelfa, Salwa (Universitas Mataram, 2025)
Educational ecotourism activities focused on high school students at the Tarakan Mangrove and Bekantan Conservation Area (KKMB) aim to increase students' awareness and knowledge of the importance of mangrove ecosystems. Through a series of interesting and interactive activities such as educational games and direct observation, participants are invited to understand the important role of mangroves as habitats for various biota, coastal protection, and carbon captured. Evaluation results show that this activity has successfully achieved its objectives. Participants showed high enthusiasm and increased understanding of mangrove ecosystems. The educational materials presented, especially educational games, were considered effective in conveying complex information in an enjoyable way. This activity was able to increase ecological understanding and awareness by 89%. However, there are still some aspects that need to be improved, such as the development of more varied educational materials and the improvement of supporting facilities for activities. Overall, this activity is a good first step in efforts to increase public awareness, especially among the younger generation, about the importance of preserving mangrove ecosystems. This activity can be used as a model for similar environmental education activities in other regions.